Novel size separation techniques for aggregates of embryonic stem cells using the Stokes equation - McAlister, William (2016)
Embryoid body formation is a commonly used procedure in embryonic stem cell differentiation as it recapitulates the early stages of embryogenesis and in doing so induces the formation of the three germ layers. Despite being a commonly used step in the differentiation of embryonic stem cells there is still a raft of inconsistencies in this process. As a result, heterogeneity exists in the cells produced in terms of their number and differentiation status; an issue which must be overcome in order to realise the full potential of embryonic stem cells for regenerative medicine. The work produced here is focussed on the issue of size heterogeneity during embryoid body formation. First of all, a closer look at the inherent size-dependent characteristics of embryoid bodies was explored over a 120-hour formation period. This showed that the mean diameter and span of embryoid bodies continued to increase throughout the duration of the 120 hours and provided insight into the population dynamics over this formation period. A non-scalable mesh separation technique was produced to further explore the inherent characteristics of embryoid bodies. This was shown to be successful at collecting size fractions of <100µm, 100-200µm and >200µm. Immunohistochemistry was used to show size-dependent differences in embryoid body differentiation by showing differential surface expression of Gata-4, Brachyury and Nestin in different sized populations. Meanwhile cell counts and a growth rate assay were performed which showed further size-dependent differences in the ability of each fraction to produce large numbers of cells. This showed that EBs within the 100-200µm fraction contained the largest numbers of cells and were the most proliferative fraction. However, they were also the only fraction to not express proteins from all three germ layers to any level. Due to the clear size-dependent differences in these size fractions perfusion technique was developed to separate embryoid bodies according to their size in a glass column. This depended on the relationship between particle diameter and terminal falling velocity. Key experimental factors that impacted on the efficacy of this technique were shown to be settled bed height, flow rate, sampling height and flow rate. As a result, two artificial neural networks were developed using a model system of Spehadex beads to show how varying these factors impacted the mean diameter and span of collected particles at a constant settled bed height. These experiments showed that this technique was limited to collecting particles from the lower reaches of the stock for both Sephadex beads and embryoid bodies. This was because the most successful factor for increasing mean diameter, flow rate, also induced the greatest increase in span. Therefore, collecting larger sized fractions reduced their discrete nature to such an extent that they were no longer distinct from one another. This suggested that this technique had potential, but was limited by the flow characteristics caused by increasing flow rate. As a result, the separation technique was adapted to overcome this by inverting the column and removing the impact of flow rate; instead allowing gravity alone to separate the particles using a top-loading method. This method was shown to be substantially more successful at collecting larger particles in discrete fractions, however, there were issues with collecting the smaller fractions during a 15-minute separation. Adaptation of this technique allowed all three size fractions to be collected effectively. Finally, a growth rate assay was performed to determine if the embryoid bodies could survive the conditions encountered in this technique and continue to grow post-separation. The cells collected from the column were able to continue growing when dissociated and grown in two-dimensional culture. However, their growth rate was lower than that in the unseparated control and it is not known whether this was because the technique is destructive. This research has therefore identified a cheap, effective, tuneable, novel size-separation technique for embryoid bodies that can collect multiple fractions in a single run with high throughput.